Predator Free 2050: A flawed conservation policy displaces higher priorities and better, evidence‐based alternatives. Issue 6 (10th July 2018) - Linklater, Wayne; Steer, Jamie
Abstract: New Zealand's policy to exterminate five introduced predators by 2050 is well‐meant but warrants critique and comparison against alternatives. The goal is unachievable with current or near‐future technologies and resources. Its effects on ecosystems and 26 other mammalian predators and herbivores will be complex. Some negative outcomes are likely. Predators are not always and everywhere the largest impact on biodiversity. Lower intensity predator suppression, habitat protection and restoration, and prey refugia will sometimes better support threatened biodiversity. The policy draws attention to where predators are easily killed, not where biodiversity values are greatest. Pest control operations are already contested and imposing the policy is likely to escalate those conflicts. While "high‐profile, " a focus on predator eradication obscures the fact that indigenous habitat cover and quality continues to decline. Thus, the policy is flawed and risks diverting effort and resources from higher environmental priorities and better alternatives. Biodiversity conservation policies should be guided by cost‐benefit analyses, prioritization schemes, and conservation planning in an adaptive management framework to deliver nuanced outcomes appropriate to scale‐ and site‐specific variation in biodiversity values and threats. The success of biodiversity sanctuary‐"spillover" landscapes, habitat restoration, and metapopulation management provide the foundation to build a better policy.